Linguistics in the Royal Commentaries of Inca Garcilaso: from traditional grammar to metapragmatic reflection (Revista de Crítica Literaria Latinoamericana, 2017)
The critical tradition around the Inca Garcilaso de la Vega has highlighted the large presence of a metalinguistic reflection in his work. This reflection includes not only grammatical digressions in a traditional sense but also encompasses pragmatic and metapragmatic issues. Taking the Comentarios Reales as an example, particularly the second part, we will see how the Inca pays special attention to the relationship between the linguistic and contextual elements in the communication among the characters of the historical narrative and how it is precisely at this level that he locates many of the problems of intercomprehension between Spaniards and Indians.
Keywords: Inca Garcilaso; grammar; pragmatics; metapragmatics; linguistics